Factors affecting clinical pregnancy in controlled ovarian hyperstimulation with GnRH-a long protocol: a retrospective cross-sectional study. (18th August 2022) - Fan, Yanli; Sun, Yi-Fei; Xu, Yue-Ming; Cao, Zi-Yu; Luo, Zhuo-Ye; Sun, Yong; Zhao, Zhi-Ming; Hao, Gui-Min; Gao, Bu-Lang
Abstract: This retrospective cross-sectional study was to investigate factors affecting clinical pregnancy in patients who received gonadotropin-releasing hormone agonist luteal phase long protocol (GnRH-a long protocol) and underwent fresh in-vitro fertilisation (IVF)/intracytoplasmic sperm injection (ICSI) embryo transfer cycle. One thousand five hundred and twenty-five patients who received GnRH-a long protocol and underwent fresh IVF/ICSI embryo transfer cycle were enrolled. The clinical pregnancy rate (63.1 vs. 22.4%, p < .05) and live birth rate (53.8 vs. 14.5%, p < .05) were significantly higher while the miscarriage rate (12.5 vs. 35.3%, p < .05) was significantly lower in the two embryo group than those in the one embryo group. The clinical pregnancy rate (48.5 vs. 64.1%, p < .05) and live birth rate (38.4 vs. 55.0%, p < .05) were significantly lower in patients older than 33.5 years than those in younger patients. The clinical pregnancy rate (52 and 60.6 vs. 79.7%, p < .05) and live birth rate (36 and 51.4 vs. 69.6%, p < .05) of the thin and mediate groups were significantly lower than those in the thick group, whereas the ectopic pregnancy rate (11.5 and 1.9 vs. 0%, p < .05) was significantly higher in the thin group than in the mediate and thick group. Multivariate logistic regression analysis showed that age (OR = 0.956, 95% CI [0.931, 0.982], p < .05), number of embryos transferred (OR = 2.491, 95% CI [1.670, 3.715], p < .05) and endometrial thickness on the transplantation day (OR = 1.124, 95% CI [1.067, 1.185], p < .05) were independent factors significantly associated with clinical pregnancy. In conclusion, endometrial thickness (>14.69 mm) on the day of transfer, two cleavage embryos transferred, and female age (≤33.5 years) are independent factors affecting clinical pregnancy outcomes in controlled ovarian hyperstimulation with GnRH-a long protocol for assisted conception. IMPACT STATEMENT: What is already known on this subject? Fresh embryo transfer cycle with GnRH-a long protocol will result in a higher pregnancy rate in controlled ovarian hyperstimulation cycles. What do the results of this study add? Endometrial thickness on the day of transfer, number of embryos transferred, and female age were independent factors affecting clinical pregnancy outcomes. What are the implications of these findings for clinical practice and/or further research? When performing a fresh IVF/ICSI embryo transfer cycle with GnRH-a long protocol for ovulation induction, the independent affecting factors should be taken into consideration.